Learning agile understanding Scrum, XP, Lean, and Kanban - Stellman, Andrew; Greene, Jennifer 1971- (O'Reilly, 2014)
Learning Agile is a comprehensive guide to the most popular agile methods, written in a light and engaging style that makes it easy for you to learn. Agile has revolutionized the way teams approach software development, but with dozens of agile methodologies to choose from, the decision to ""go agile"" can be tricky. This practical book helps you sort it out, first by grounding you in agile's underlying principles, then by describing four specific-and well-used-agile methods: Scrum, extreme programming (XP), Lean, and Kanban. Each method focuses on a different area of development, but they
Includes index. - Print version record
Keywords: Agile software development; Méthodes agiles (Développement de logiciels); COMPUTERS; Programming; General; COMPUTERS; Software Development & Engineering; General